Viscoelastic Properties of Filled Polyurethane Auxetics - Shevchuk, T.M.; Bordyuk, M.A.; Krivtsov, V.V.; Kukla, V.V.; Mashchenko, V.A. (Physics and Chemistry of Solid State, 2021)
The paper presents experimental values of lateral and extension transmission ultrasonic waves speed and their absorbance coefficient obtained with the help of discrete immersed method in metal filled polymer auxetic samples with polyurethane matrix. Poisson’s ratio, real and imaginary parts of complex dynamic elastic modulus (Young’s modulus, shear modulus, bulk modulus) and mechanical losses tangent of angle for extension, lateral and bulk deformation have been calculated regarding paper’s results. Viscoelastic properties of polyurethane auxetic have been examined regarding different theoretical approaches. To support negative values of Poisson’s ratio, a filled polymer model with critical filler amount and auxetic deformation models have been used. Models structural characteristics for filled polyurethane auxetics have been defined. Systems modeling with solid bulky inclusions, that are able to absorb and to disseminate ultrasonic waves, enables to consider suchlike systems as complex density materials. It is shown that in certain ratio of wave parameters and environment structural and mechanical properties, resonance effects take place, regarding filler’s particles vibration as inclusions in general.